Changes in Preventative Health Care after Medicaid Expansion - Tummalapalli, Sri Lekha (Med Care, 2020)
BACKGROUND: Medicaid expansion substantially increased health insurance coverage, but its effect on the delivery of preventative health care is unclear. OBJECTIVES: To assess the impact of Medicaid expansion on the receipt of 15 different measures of preventive care including cancer screening, cardiovascular risk reduction, diabetes care, and other primary care measures. RESEARCH DESIGN: We performed a serial cross-sectional analysis of BRFSS survey data from 2012 to 2017. We used a quasi‐experimental design with difference‐in‐differences (DiD) analyses to examine changes in preventative health care delivery over three time periods in Medicaid expansion compared with non-expansion states. SUBJECTS: We included low-income (<138% FPL) non-elderly (age<65) adults residing in 46 U.S. states. MEASURES: Our predictor was residing in a Medicaid expansion state (24 states) versus non-expansion state (19 states). Our primary outcomes were preventative health care services, which we categorized as cancer screening (breast cancer, cervical cancer, and colorectal cancer); cardiovascular risk reduction (serum cholesterol screening in low-risk groups, serum cholesterol monitoring in high-risk groups, and aspirin use); diabetes care (serum cholesterol monitoring, Hemoglobin A1c monitoring, foot examination, eye examination, and influenza vaccination, and pneumonia vaccination), and other primary care measures (influenza vaccination, alcohol use screening, and HIV screening). RESULTS: Survey responses from 500,495 low-income non-elderly adults from 2012 to 2017 were included in the analysis, representing 68.2 million U.S. adults per year. Of the 15 outcomes evaluated, we did not detect statistically significant differences in cancer screening (3 outcomes), cholesterol screening or monitoring (2 outcomes), diabetes care (6 outcomes), or alcohol use screening (1 outcome) in expansion compared to non-expansion states. Aspirin use (DiD 8.8%, p<0.001), influenza vaccination (DiD 1.4%, p = 0.016), and HIV screening (DiD 1.9%, p = 0.004) increased in expansion states compared to non-expansion states. CONCLUSIONS: Medicaid expansion was associated with an increase in aspirin use, influenza vaccination, and HIV screening in expansion states. Despite improvements in access to care, including health insurance, having a primary care doctor, and routine visits, Medicaid expansion was not associated with improvements in cancer screening, cholesterol monitoring, diabetes care, or alcohol use screening. Our findings highlight implementation challenges in delivering high quality primary care to low-income populations.